1998
DOI: 10.1046/j.1471-4159.1998.71062487.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Functional Anaphylatoxin C3a Receptor by Astrocytes

Abstract: Human astrocyte cell lines reportedly contain a specific receptor for the complement anaphylatoxin C3a based on ligand‐binding studies, functional responses, and RNA analysis by RT‐PCR. Uptake of 125I‐C3a by astrocytes was specific and reversible. Scatchard analysis indicated the presence of two classes of binding sites. High‐affinity binding sites were abundantly expressed (20,000–80,000 sites per cell) with an estimated KD of 1–2 nM. Low‐affinity binding sites with a KD of 209 nM were largely expressed (n≥ 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 21 publications
6
42
0
1
Order By: Relevance
“…In vitro studies on cultured cells confirmed the expression of C3aR and C5aR by cerebellar granule neurons; (i) measurement of C3aR and C5aR mRNAs revealed maximum expression of both receptor genes at DIV 2, and (ii) flow cytometry and immunocytochemical experiments showed that the C3aR and C5aR proteins occurred in the majority of granule cells from DIV 4 to DIV 9. Up to now the presence of C3aR and C5aR has been documented in the adult rodent brain, where the two receptors are expressed by glial cells, astrocyte (11)(12)(13), and microglia (14,15). C3aR and C5aR are present both in vitro (11)(12)(13)(14) and in vivo (15) and are upregulated in these cells after inflammation (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies on cultured cells confirmed the expression of C3aR and C5aR by cerebellar granule neurons; (i) measurement of C3aR and C5aR mRNAs revealed maximum expression of both receptor genes at DIV 2, and (ii) flow cytometry and immunocytochemical experiments showed that the C3aR and C5aR proteins occurred in the majority of granule cells from DIV 4 to DIV 9. Up to now the presence of C3aR and C5aR has been documented in the adult rodent brain, where the two receptors are expressed by glial cells, astrocyte (11)(12)(13), and microglia (14,15). C3aR and C5aR are present both in vitro (11)(12)(13)(14) and in vivo (15) and are upregulated in these cells after inflammation (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now the presence of C3aR and C5aR has been documented in the adult rodent brain, where the two receptors are expressed by glial cells, astrocyte (11)(12)(13), and microglia (14,15). C3aR and C5aR are present both in vitro (11)(12)(13)(14) and in vivo (15) and are upregulated in these cells after inflammation (15)(16)(17). In situ hybridization and immunohistochemistry analysis also revealed a constitutive expression of mouse and rat C3aR in cortical and hippocampal neurons (17,19) as well as in cerebellar Purkinje cells (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of anaphylatoxins to extracellular, N-terminal regions of the anaphylatoxin receptors allows conformational changes to the intracellular, C-terminal regions of the receptors, resulting in coupling to G-proteins, predominantly pertussis toxin-sensitive G iα , to induce downstream signaling cascades [61][62][63][64][65]. Activities of anaphylatoxins are confined by cell types that express their receptors, predominantly thought to be cells of myeloid origin, including granulocytes (basophils, eosinophils, and neutrophils), monocytes/macrophages, mast cells, and some dendritic cells, although there are numerous reports of receptor expression in a number of nonmyeloid cell types [54,59,60,[66][67][68][69][70][71][72][73]. Inactivation of anaphylatoxin molecules is an important determinant of the duration and extent of their potent functions and represents an alternative mechanism to control complement activation.…”
Section: Effectors Of the Complement Systemmentioning
confidence: 99%
“…This receptor is expressed on a large variety of cells as of myeloid origin like mast cells, basophils, neutrophils, eosinophils, monocytes-macrophages, dendritic cells and microglia [55][56][57][58][59][60], as well as in non-myeloid cells like astrocytes [61,62], endothelial cells [63], and epithelioid cells, smooth muscle cells and parenchymal cells [64]. The presence of C3aR on activated but not non-activated T lymphocytes has also been reported [65].…”
Section: Anaphylatoxins Receptorsmentioning
confidence: 99%